c0+c1+c2+c3=0 c1+c2*2*h+c3*3*h=1 2*h=h^2*c1+4*h^2*c2+c3*9*h^2 12*h^2=c1*h^3+c2*8*h^3+27*h^3*c3

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:
53 уравнение:
54 уравнение:

Примеры

Решение

Вы ввели [src]
c0 + c1 + c2 + c3 = 0
$$c_{3} + c_{2} + c_{0} + c_{1} = 0$$
c1 + c2*2*h + c3*3*h = 1
$$h 3 c_{3} + c_{1} + h 2 c_{2} = 1$$
       2         2            2
2*h = h *c1 + 4*h *c2 + c3*9*h 
$$2 h = h^{2} \cdot 9 c_{3} + c_{1} h^{2} + c_{2} \cdot 4 h^{2}$$
    2       3         3       3   
12*h  = c1*h  + c2*8*h  + 27*h *c3
$$12 h^{2} = c_{3} \cdot 27 h^{3} + c_{1} h^{3} + h^{3} \cdot 8 c_{2}$$
Быстрый ответ
$$c_{11} = - \frac{4}{2 h - 3}$$
=
$$- \frac{4}{2 h - 3}$$
=
-4/(-3 + 2*h)

$$c_{21} = \frac{- h + \frac{9}{2}}{h \left(2 h - 3\right)}$$
=
$$\frac{- h + \frac{9}{2}}{h \left(2 h - 3\right)}$$
=
(4.5 - h)/(h*(-3 + 2*h))

$$c_{01} = \frac{22 h - 11}{6 h \left(2 h - 3\right)}$$
=
$$\frac{22 h - 11}{6 h \left(2 h - 3\right)}$$
=
1.83333333333333*(-1 + 2*h)/(h*(-3 + 2*h))

$$c_{31} = \frac{4 h - 8}{3 h \left(2 h - 3\right)}$$
=
$$\frac{4 h - 8}{3 h \left(2 h - 3\right)}$$
=
1.33333333333333*(-2 + h)/(h*(-3 + 2*h))
×

Где учитесь?

Для правильного составления решения, укажите: